2013
DOI: 10.1103/physrevx.3.011021
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Transport in Sketched Nanostructures at theLaAlO3/SrTiO3Interface

Abstract: The oxide heterostructure LaAlO 3 =SrTiO 3 supports a two-dimensional electron liquid with a variety of competing phases, including magnetism, superconductivity, and weak antilocalization because of Rashba spin-orbit coupling. Further confinement of this two-dimensional electron liquid to the quasi-onedimensional regime can provide insight into the underlying physics of this system and reveal new behavior. Here, we describe magnetotransport experiments on narrow LaAlO 3 =SrTiO 3 structures created by a conduct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…Our calculations -both large-N and DMRG -show that our model gives rise to a helical wire. Remarkably, recent transport measurements can be interpreted as evidence that 1D channels at the LAO/STO interface are helical wires 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Our calculations -both large-N and DMRG -show that our model gives rise to a helical wire. Remarkably, recent transport measurements can be interpreted as evidence that 1D channels at the LAO/STO interface are helical wires 50 .…”
Section: Discussionmentioning
confidence: 99%
“…This is most clear from the experiments by Cen et al [14][15][16][17][18] in which it was shown that regions of 2DEG at the buried interface can be induced by modifying the surface adsorbates with an appropriately biased atomic force microscopy (AFM) tip.…”
mentioning
confidence: 91%
“…Electron correlations are believed to play a crucial role in determining the physics of this system that has been defi ned as a "2D electron liquid," 22 where electrons interact and can no longer be viewed as free electrons without interactions, and includes in its phase diagram superconductivity, 23 magnetism 24 (also coexisting with superconductivity itself), 25 -28 a semiconducting/ insulating state, 29 -31 negative compressibility, 32 a high mobility metallic state exhibiting quantum transport, 33 -35 including nonlocal transport, 36 and so-called Rashba-induced spin-orbit coupling leading to additional splitting of the d -bands (details can be found in Reference 37 ).…”
Section: Phase Diagrams and Electron Correlationsmentioning
confidence: 99%